The Role of Brand Image in Mediating the Effect of Social Media Marketing and Electronic Word of Mouth on Purchase Decisions (A Study on Uniqlo Product Buyers in Bali Province) - I Gede Adi Sucitha; Ni Ketut Seminari; I Gusti Ayu Ketut Giantari; I Gusti Ngurah Jaya Agung Widagda (PT. Publikasiku Academic Solution, 2026)
Abstract: In the competitive fashion industry, Uniqlo's fluctuating performance during the 2021–2024 period and preliminary survey results indicating low purchase decisions in Bali highlight the importance of strengthening the factors that influence consumer purchasing decisions. This study aims to examine the effect of social media marketing and E-WOM on purchase decisions on Uniqlo brand product buyers in Bali Province, with brand image as a mediating variable. The research was conducted among consumers in Bali who had previously purchased Uniqlo products. A total of 135 samples were obtained using purposive sampling. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results reveal that social media marketing and E-WOM exert a positive and significant influence on purchase decisions. Furthermore, both variables also demonstrate a positive and significant impact on brand image. Brand image, in turn, is found to significantly affect purchase decisions and serves as a mediating variable in the relationship between social media marketing, E-WOM, and purchase decisions. Based on these findings, it is recommended that the company optimize its social media marketing strategy by delivering engaging and interactive content, as well as encouraging the spread of positive E-WOM across various online platforms. The brand image can be strengthened by emphasizing product quality, modern design, comfort, and affordable pricing.